The village world of early medieval Northern Spain : local community and the land market - Portass, Robert, 1983- (Suffolk : Boydell & Brewer, 2017)
In the early eighth century, the Muslim general Tariq ibn Ziyad led his forces across the Straits of Gibraltar and conquered most of the Iberian Peninsula. However, alongside the flourishing kingdom of al-Andalus, the small Christian realm of Asturias-León endured in the northern mountains. This book charts the social, economic and political development of Asturias-León from the Islamic conquest to 1031. Using a forensic comparative method, which examines the abundant charter material from two regions of northern Spain - the Liébana valley in Cantabria, and the Celanova region of southern Galicia - it sheds new light on village society, the workings of government, and the constant swirl of buying, selling and donating that marked the rhythms of daily life. It also maps the contact points between rulers and ruled, offering new insights on the motivations and actions of both peasant proprietors and aristocrats. Robert Portass is Senior Lecturer in Medieval History at the University of Lincoln.
Frontcover; Contents; List of illustrations; Acknowledgements; Abbreviations; Note on names, place names and spellings; Introduction: The making of medieval Iberia, 711-1031; PART I: THE LIÉBANA; 1 Cantabria after Rome; 2 Local society in the ninth century; 3 The emergence of a village elite; 4 Kings, counts and courts; PART II: SOUTHERN GALICIA; 5 Galicia after Rome; 6 Before Celanova; 7 Rosendo, Celanova and the village world, 936-1031; 8 Magnates, monasteries and the public framework; Conclusion; Bibliography; Index.
Title from publisher's bibliographic system (viewed on 06 Sep 2017).
JSTOR
Keywords: Liébana Region (Spain) -- Economic conditions -- 711-1516.; Orense (Spain : Province) -- Economic conditions -- 711-1516.; Liébana Region (Spain) -- Social conditions -- 711-1516.; Orense (Spain : Province) -- Social conditions -- 711-1516.; Liébana Region (Spain) -- Politics and government -- 711-1516.; Orense (Spain : Province) -- Politics and government -- 711-1516.; Liébana Region (Spain) -- History -- 711-1516.; Orense (Spain : Province) -- History -- 711-1516.; HISTORY -- Medieval; HISTORY -- Europe -- Spain & Portugal; Economic history; Politics and government; Social conditions; Spain -- Liébana Region; Spain -- Orense (Province); 711-1516; History